2017
DOI: 10.3389/fnins.2017.00323
|View full text |Cite
|
Sign up to set email alerts
|

Maturation, Behavioral Activation, and Connectivity of Adult-Born Medium Spiny Neurons in a Striatal Song Nucleus

Abstract: Neurogenesis continues in the adult songbird brain. Many telencephalic song control regions incorporate new neurons into their existing circuits in adulthood. One song nucleus that receives many new neurons is Area X. Because this striatal region is crucial for song learning and song maintenance the recruitment of new neurons into Area X could influence these processes. As an entry point into addressing this possibility, we investigated the maturation and connectivity within the song circuit and behavioral act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 76 publications
2
21
0
Order By: Relevance
“…6). Together with our previous data we conclude that reaching low FoxP2 levels is a sign that adult-born born MSN in Area X have reached maturity by 6 weeks after their generation in the VZ 34 . Since our previous work demonstrated that new MSNs participate in singing-associated neural activity in Area X 34 here we asked if this was linked to FoxP2 levels.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…6). Together with our previous data we conclude that reaching low FoxP2 levels is a sign that adult-born born MSN in Area X have reached maturity by 6 weeks after their generation in the VZ 34 . Since our previous work demonstrated that new MSNs participate in singing-associated neural activity in Area X 34 here we asked if this was linked to FoxP2 levels.…”
Section: Discussionsupporting
confidence: 86%
“…Together with our previous data we conclude that reaching low FoxP2 levels is a sign that adult-born born MSN in Area X have reached maturity by 6 weeks after their generation in the VZ 34 . Since our previous work demonstrated that new MSNs participate in singing-associated neural activity in Area X 34 here we asked if this was linked to FoxP2 levels. After singing FoxP2 mRNA and protein levels are lower in Area X tissue [25][26][27] than when birds were silent whereas the expression of the immediate early gene EGR-1 increases linearly the more birds sing undirected song 40,41 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…DARPP-32 is a reliable marker of dopaminoceptive neurons in both mammals (Hemmings, et al, 1987) and zebra finches Kosubeck-Langer, et al, 2017). To determine whether DARPP-32+ HVC NNs receive catecholaminergic input, we labeled tyrosine hydroxylase, the rate-limiting enzyme in the catecholamine synthetic pathway (Fernstrom & Fernstrom, 2007).…”
Section: Darpp-32+ Hvc Nns Receive Catecholaminergic Inputmentioning
confidence: 99%